PENGARUH RETURN ON ASSET, DEBT TO EQUITY RATIO DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI MAKANAN DAN MINUMAN DI BEI - Rahmah Yulianti; Khairunna (Jurnal Penelitian Ekonomi Akuntansi, 2020)
This research was conducted with the aim of knowing the effect of return on assets, debt to equity ratio and return on equity to stock prices. This study uses secondary data in the form of time horizon data. This research is a combination of cross-sectional studies with longitudinal studies (timeseries) called panel data or pooled data from 2017 to 2019. This research uses quantitative descriptive analysis method by looking at the effect of return on assets, debt to equity ratio and return on equity. The method of collecting data in this study is by means of documentation, namely in the form of financial statement data for manufacturing companies in the Food and Beverage Industry sector which are listed on the IDX. The results showed that the return on assets has an effect on stock prices with the acquisition coefficient of 0.319, indicating that the effect of return on assets on stock prices is not equal to zero (β2 ≠ 0), the Debt To Equity Ratio has an effect on stock prices with the acquisition coefficient value of 0.442, indicating that the effect of the Debt To Equity Ratio on stock prices is not equal to zero (β3 ≠ 0). Return on Equity has an effect on stock prices with the acquisition coefficient value of 0.644, indicating that the effect of return on equity on stock prices is not equal to zero (β4 ≠ 0). Return On Asset, Debt To Equity Ratio and Return On Equity together have quite a strong influence on stock prices, namely 75.5%, while 24.5% is explained by other variables not explained in this study.